The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.4049/jimmunol.168.3.1457
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Agonistic Anti-4-1BB Monoclonal Antibody Leads to the Amelioration of Experimental Autoimmune Encephalomyelitis

Abstract: 4-1BB, a member of the TNFR superfamily, is a costimulatory receptor primarily expressed on activated T cells. It has been shown that the administration of agonistic anti-4-1BB Abs enhances tumor immunity and allogenic immune responses. Paradoxically, we found that the administration of an agonistic anti-4-1BB mAb (2A) dramatically reduced the incidence and severity of experimental autoimmune encephalomyelitis (EAE). Adoptive transfer of T cells from such treated mice failed to induce EAE, whereas anti-4-1BB t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
149
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(160 citation statements)
references
References 38 publications
8
149
0
2
Order By: Relevance
“…Using TCR transgenic DO11.10 mice, we found that administration of agonistic anti-CD137 initially promoted Ag-specific CD4 ϩ T cell proliferation, but subsequently accelerated their depletion by inducing apoptosis. In accordance, in an experimental autoimmune encephalomyelitis model, such treatment initially up-regulated autoreactive Th1 cell functions before down-regulating the overall response (36). These studies suggest the diametric effect of CD137 costimulation on CD4 ϩ T cells.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Using TCR transgenic DO11.10 mice, we found that administration of agonistic anti-CD137 initially promoted Ag-specific CD4 ϩ T cell proliferation, but subsequently accelerated their depletion by inducing apoptosis. In accordance, in an experimental autoimmune encephalomyelitis model, such treatment initially up-regulated autoreactive Th1 cell functions before down-regulating the overall response (36). These studies suggest the diametric effect of CD137 costimulation on CD4 ϩ T cells.…”
Section: Discussionsupporting
confidence: 54%
“…They found that adoptive transfer of T cells from SRBCimmunized and anti-CD137-treated mice along with B cells from untreated mice into C.B-17 SCID mice failed to generate an anti-SRBC IgG response, whereas the opposite combination produced normal primary and secondary humoral responses to SRBC, isolating the defect to T cells. However, the lack of a CD4 ϩ T cell response can also be explained by the diminished CD4 ϩ T cells after initial activation, because our earlier study showed that such treatment can induce an initial activation, followed by activationinduced cell death (36). Using TCR transgenic DO11.10 mice, we found that administration of agonistic anti-CD137 initially promoted Ag-specific CD4 ϩ T cell proliferation, but subsequently accelerated their depletion by inducing apoptosis.…”
Section: Discussionmentioning
confidence: 80%
“…It has been described that the agonistic anti-CD137 antibodies in vivo have a preferential role as a costimulation molecule for CD8 + T cells, with no detectable effect on CD4 + T cells [34][35][36]51]. Moreover, some experiments have suggested that CD137 stimulation might induce CD4 + T cell anergy [52,53] or activationinduced T cell death [54]. However, there are several reports in in vitro models supporting the costimulatory effect of CD137 on CD4 + T cell proliferation and survival activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several reports in in vitro models supporting the costimulatory effect of CD137 on CD4 + T cell proliferation and survival activation. [34,50,[54][55][56][57][58]. In addition, recent reports using TCR transgenic mice show a positive role of CD137 in CD4 + T cell activation in vivo [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons might be the promiscuous expression of 4-1BB on many kinds of immune cells that have specific and perhaps opposing roles in various pathophysiological circumstances. For example, it has been suggested that negative effects of anti-4-1BB could be due to promoting apoptosis of CD4 cells (34,61), and that CD4 and CD8 cells respond differently to 4-1BB ligation (58). Alternatively, anti-4-1BB has been proposed to induce regulatory cells, either in the CD8 lineage (31,62), or in the dendritic cell lineage (30).…”
Section: Discussionmentioning
confidence: 99%